When and how do we stop antifungal treatment for an invasive mould infection in allogeneic haematopoietic cell transplant recipients?. Issue 11 (25th July 2022) - Roth, Romain Samuel; Masouridi‐Levrat, Stavroula; Giannotti, Federica; Mamez, Anne‐Claire; Morin, Sarah; van Delden, Christian; Chalandon, Yves; Neofytos, Dionysios
Abstract: Background: Limited data exist to describe end‐of‐treatment (EOT) parameters of antifungal therapy for invasive mould infections (IMI). Methods: In a 10‐year cohort of consecutive adult allogeneic haematopoietic cell transplant recipients with proven/probable IMI, we describe treatment duration and patient profile at EOT. Results: There were 61 patients with 66 proven/probable IMI identified: 47/66 (71%) invasive aspergillosis (IA), 11/66 (17%) mucormycosis, and 8/66 (12%) other‐IMI. Excluding 5 (8%) patients lost to follow‐up, treatment was prematurely discontinued due to death or palliative care in 29/56 (51.8%) patients. Antifungal treatment was completed in 27 (48.2%) patients, for a median duration of 280 days (IQR: 110, 809): 258 (IQR: 110, 1905) and 307.5 (99, 809) days in IA and non‐IA IMI, respectively. Treatment was continued after 90 and 180 days in 43/56 (76.8%) and 30/56 (53.6%) patients, respectively. At EOT, most patients were not neutropenic (ANC: 2.12 G/L, IQR: 0.04, 5.3), with CD4+ counts at 99 cells/μl (IQR: 0, 759) and immunoglobulins at 5.6 g/L (IQR: 2.3, 10.6). Most patients (16/27, 59.3%) were not receiving steroids at EOT, while 14/27 (53.9%) were on another type of immunosuppression. Amongst 15 patients with imaging at EOT, 12 (80%) had complete/partial radiologic response. Any chart documentation or an infectious disease consultation on treatment discontinuation was observed in 12/56 (21%) and 11/56 (20%) patients, respectively. Conclusions: Long treatment courses are observed in patients with IMI, due to prolonged immunosuppression. Although immune reconstitution and radiological response were frequently observed at EOT, consistent documentation of treatment discontinuation based on well‐defined parameters is lacking.